# Aptitude - Surds and Indices - Discussion

Discussion Forum : Surds and Indices - General Questions (Q.No. 2)

2.

If | a |
x - 1 |
= | b |
x - 3 |
, then the value of x is: |
||||

b |
a |

Answer: Option

Explanation:

Given | a |
x - 1 |
= | b |
x - 3 |
|||

b |
a |

a |
x - 1 |
= | a |
-(x - 3) |
= | a |
(3 - x) |
|||||||

b | b | b |

*x* - 1 = 3 - *x*

2*x* = 4

*x* = 2.

Discussion:

26 comments Page 1 of 3.
Pooja said:
1 decade ago

I didn't understand for solve the method. Please explain.

Ravi kiran said:
1 decade ago

@pooja

(b/a) can be written as (a/b)^-1.

Based on this concept this problem is solved.

(b/a) can be written as (a/b)^-1.

Based on this concept this problem is solved.

Nem prasad said:
1 decade ago

Can anybody tell me what is the concept through which this problem has been solved ?

Basavaraju said:
1 decade ago

I can not understand.

Nisikanta said:
1 decade ago

(a/b)^x-1= (b/a)^x-3

* Remember, sinplification is always solved by 2 or more fraction or number or alphabet.

:If the alphabet fraction is not equal to one anthor,we have reranged it.

= (a/b)^x-1= (a/b)^-(x-3)= (a/b)^(3-x)

: Then we have to take power for simplification.

= x-1= 3-x

* When the number goes after or before '=' sign the sign changes

: Now we have to change the places.

= 2x=4

=x=2

* Remember, sinplification is always solved by 2 or more fraction or number or alphabet.

:If the alphabet fraction is not equal to one anthor,we have reranged it.

= (a/b)^x-1= (a/b)^-(x-3)= (a/b)^(3-x)

: Then we have to take power for simplification.

= x-1= 3-x

* When the number goes after or before '=' sign the sign changes

: Now we have to change the places.

= 2x=4

=x=2

Yashi Jain said:
1 decade ago

How could you add the powers when there is an = sign between the two.

Rakesh KIIT said:
1 decade ago

(a/b)^x-1=(b/a)^x-3

can be written as :

After cross multiplication :

(a)^(2x-4)=(b)^(2x-4)

=>(a/b)^(2x-4)=1

=>(a/b)^(2x-4)=(a/b)^0

=> 2x-4=0

=>x=4/2

=>x=2

can be written as :

After cross multiplication :

(a)^(2x-4)=(b)^(2x-4)

=>(a/b)^(2x-4)=1

=>(a/b)^(2x-4)=(a/b)^0

=> 2x-4=0

=>x=4/2

=>x=2

SANJIV KUMAR said:
9 years ago

Everybody can you tell me that how cross multiplication (a)^(2x-4) = (b)^(2x-4) in this answer.

Manu said:
9 years ago

The problem can be solved by using the property "If the bases are equal then there powers must be equal". So in order to find the value we have to make the bases equal, after equating solve for x.

Faheem said:
9 years ago

Any one can explain in detail.

Post your comments here:

Quick links

Quantitative Aptitude

Verbal (English)

Reasoning

Programming

Interview

Placement Papers